KODE – KODE DALAM AKTIVITAS MENYELAM - Kembuan, Ester Magdalena (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Semiotics is a study about signs. A Sign is something that can be found in some different forms such as verbal or nonverbal, written or unwritten. They can be anything that convey meaning such as words on papers, pictures, drawings, and gestures or codes. In this research, the writer takes the gestures codes used by diving activity as the object of research.Codes also can be found in gestures for example in diving activity. In this category, codes are used in diving activity for communication. The problems in this research, what are the forms of codes used by Manado’s diver in diving activity, and what are the meaning of codes in diving activity. The purpose of the research is to identify, analyze, and classification the codes in diving activity. The data about codes are collected by getting some information from informants, and the data pictures of international and local codes were collected at dive spot at Malalayang II seashore.All the collected data are analyzed based on Peirce theory of signs and codes, and the analysis used is descriptive analysis. The results of this research show that there are 17 codes international, and also 9 local codes In Manado that usually using by local divers in Manado. The form of International codes there are 5 classification of codes, direction codes, sea species codes, safety codes, secure problem codes, and attention codes. The form of local codes there are 4 classification of codes, sea species codes, safety codes, secure codes and attention codes. and the meanings of codes are, how to show to buddy about the condition when the diver look, give a clue, or feel something inside water and codes are the way the diver give information with fellow while diving activity. Keywords: Diving Codes, Descriptive Analysis, Semiotics.